Answer:
24
Step-by-step explanation:
2:6
1:3
24:72
The correct answer is maybe 3
-4(x-1)=-3x+13-9-x
-4x+4=-3x+4-x
-4x+4=-4x+4
-4x=-4x
0=0
Answer:
10x - 5 / 4
Step-by-step explanation:
15 - ( -10x ) - 20 / ( 12 + ( -8 ) )
= ( -5 ) + 10x / ( 4 )
= 10x - 5 / 4
<em>Hope it helps</em>
<em>:D</em>
Answer:
2 and -3
Step-by-step explanation:
because a coefficient is a numerical or constant quantity placed before and multiplying the variable in an algebraic expression (e.g. 4 in 4x).
so in 2x-3y+5, 2 and -3 are the coefficients.